Analysis of Judge's Ruling Number: 45/Pdt.G/2020/PN.Pwd Concerning Violation of Individual Guaranteed Land - Osila Rama Sagita; Moh. Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Decision Number: 45/Pdt.G/2020/PN.Pwd is the final result of a conflict that occurred between Paryadi and PT BRI, KPKNL, and Notary Moch Farchan Ali Imaron. This conflict occurred when Paryadi borrowed a sum of money from BRI with a land certificate as collateral, then several times it turned out that Paryadi was unable to keep up with the installments that were supposed to be made. BRI then held an auction for the land and finally sold it. It turned out that the auction did not reveal Paryadi as the original owner of the land, so this case was brought to court. On the one hand, the court paid attention to the flaws in the auction carried out by BRI and KPKNL which could result in the auction being null and void, but in terms of evidence, Paryadi was unable to provide evidence that was strong enough to defend himself. And in this agreement, it turns out that there are many things that are considered flawed and can make an agreement flawed and null and void. This research uses a normative juridical method, which uses a legal approach which is the basis for an agreement to occur.